(untitled) (Equilibrium: Jurnal Pendidikan, 2022)
This study aims to determine the student’s perception of effectiveness Google platform in online learning in English for student grade XI. The Google platform comes from belajar.id it is an account launched by the Ministry of Education and Culture and Information Technology Centre for support the learning process as long as online learning. In addition, this research also aims for the quality of online learning in learning English that has been carried out during the covid-19 pandemic. The research method used is quantitative with a survey method. The samples of this study is 30 students. Data collection using the method survey with a likert scale. Data analysis by calculating the percentage of data on each indicator, then from the presentation of the data an analysis is carried out descriptively on each indicator. The results showed that the effectiveness of online learning in English in Covid-19 pandemic situation at SMA Muhammadiyah Tanah Grogot. The results of this study are also expected to be a recommendation for applications that can be used in learning English subjects during the pandemic and as study material for further research related to the effectiveness of online learning.